Application of the type-2 fuzzy logic controller and the fractional order controller to regulate the DTC speed in an induction motor - Mabrouk, Younes Abdelbadie; Mokhtari, Bachir; Allaoui, Tayeb (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: Among excellent strategies available to control the torque of asynchronous motors, we distinguish direct torque control. This technique of control allows direct control of magnetic flux and electromagnetic torque without the need to decouple them. Also, direct torque control like each control strategy has some drawbacks, the major drawbacks of this technique being operation at a variable switching frequency and flux and electromagnetic ripples due to the use of hysteresis regulators. It worsens acoustic noise, especially at low speeds, as well as the control performances.Methods: To improve the performance of direct torque control especially at low speeds, the authors propose using fractional order PID in combination with type-2 fuzzy logic controllers to regulate the speed of an induction motor controlled by direct torque control.Results: The results obtained by the proposed regulators show the improvements made to the system.Conclusion: The proposed contribution can exert better control efforts.
Keywords: direct torque control (DTC); fuzzy logic controller (FLC); fractional order controller (FO); induction motor (IM); FFT analysis